The Use of Mindmaps and its Effectiveness in ELT: A Systematic Review - Rahayu, Ainaya; Apriani, Resty Nur; Adi Permata , Mariyam Syahana; Ramadhanti , Putri; Tarihoran , Naf'an (PT FORMOSA CENDEKIA GLOBAL, 2024)
The systematic review examines the effectiveness of incorporating mind maps into English Language Teaching (ELT) classrooms. The goal is to analyze the impact of mind maps on various aspects of student learning, including vocabulary mastery, reading comprehension, and writing skills. Studies published from 2018 to 2023 in scientific databases such as Google Scholar, ERIC, and Mendeley. A rigorous search strategy will be used to identify relevant research investigating the use of mind maps in ELT contexts. This review will synthesize the findings to evaluate the overall influence of mind maps on student achievement in ELT. It is hoped that this comprehensive analysis will provide valuable insights for ELT practitioners, by uncovering the potential benefits and drawbacks of using mind maps on various aspects of student learning, including vocabulary mastery, reading comprehension, and writing skills. This review aims to inform teaching practice and identify areas for further research to optimize their effectiveness in enhancing language learning